Analysis of Pesticide Residues in Agricultural Soil via GC-MS and Enhancement of Degradation Efficiency by Bacillus velezensis SKRB5 - Sreelaxmi Kadarla; Rajani. B (The Bioscan, 2024)
Overuse of pesticides negatively impacts soil fertility and ecosystems. This study aimed to screen agricultural soils in Mahabubabad, Telangana, India, for pesticide residues using GC-MS techniques and to identify bacteria capable of degrading these pesticides. The findings revealed three major pesticides: Monocrotophos, Atrazine, and Mancozeb. Among ten bacterial isolates, Bacillus velezensis SKRB5 demonstrated significant pesticide degradation ability. The growth and biodegradation capacity of Bacillus velezensis SKRB5 varied significantly across different pH values, temperatures, and pesticide concentrations. Optimal growth conditions were identified as pH 7, 37°C, and a pesticide concentration of 250 mg/L. Enzyme activity analysis over a week showed peak degradation on the fourth day, with Phosphotriesterases activity reaching 750 U/mg for Atrazine and Phosphatases activity reaching 600 U/mg for Mancozeb and Monocrotophos. This research highlights the importance of enzymatic activity in biodegradation and supports the future application of Bacillus velezensis SKRB5 in environmental remediation.